W kwestii wcześniejszych założeń kościoła św. Jana we Włocławku - Wojda, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 1983)
The Institute of Archaeology of Ш 4 university has been conducting the complex archaeological investigations of the urban aglomeration in Włocławek since 1976. The purpose of these works is to receive a full picture of the significance site by confronting the archaeological sources with the historical, Cartographical ones and with the . architectonical ascertainments. The first stage of research covers the investigation of the medieval town, i.e. present Old Town. The former investigations were concentrated within the Old Market, where the gothic church of St. John, built in 1538, is situated. They aimed at stating whether this church – according to the accepted M. Morawski'a opinion – was founded upon, or contains inside, the fragments of the earlier, it is believed, romanistic St. John's church. In a course of the excavations carried out. in the ditches running along the Southern wall of an apse and along the northern wall of the church between the aisle and sacristy no remains of the earlier wall of stones or bricks were revealed. Moreover, the finds gained during the archaeological works in the Old Market allow one to date the beginnings of local habitation to the late 13th and 14th century. After having confronted the above ascertainments with the written sources one can suppose that the earlier St. John's church must have been situated closer to the stronghold, i.e. on the area of the earlier habitation datable» prior to the 13th century. This hypothesis is moreover supported by the regularities in development of Włocławek habitation, which extended along the West-East line, i.e. from the stronghold towards the Old Town.